2006
DOI: 10.1016/j.biopsych.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Levels and Hippocampus Volumes in Healthy Preadolescent Children

Abstract: Background-Research in animal models has demonstrated that elevated levels of glucocorticoids can inflict damage within the hippocampus. In adult humans, elevated cortisol levels have been associated with reduced hippocampal volumes; however, normative data in children are not available. The objective of this study was to examine possible associations of serum cortisol levels with hippocampal volumes and morphology in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…First, the pattern of our shape analysis shows a partial overlap with findings from a previous study of hippocampal morphology and cortisol levels in children (Wiedenmayer et al, 2006). They also reported clusters at the subiculum on the dorsal surface at the head of the right hippocampus, and at the dentate gyrus.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…First, the pattern of our shape analysis shows a partial overlap with findings from a previous study of hippocampal morphology and cortisol levels in children (Wiedenmayer et al, 2006). They also reported clusters at the subiculum on the dorsal surface at the head of the right hippocampus, and at the dentate gyrus.…”
Section: Discussionsupporting
confidence: 52%
“…Seckl et al, 1991, López et al, 1998, Medina et al, 2013, Wang et al, 2013) and some rodent studies have identified effects of GC exposure specifically in subregions Cornu Ammonis (CA1) and CA3 only (reviewed in McEwen, 2007); hence it is plausible that humans may also exhibit regional associations with cortisol levels. Among healthy children (n = 17, age range 7–12 years; Wiedenmayer et al, 2006), higher cortisol levels were not associated with hippocampal volume, but were associated with outward deformations in the subiculum on the dorsal surface at the head of the right hippocampus and at the dentate gyrus, and with inward deformations along the lateral aspects of the medial hippocampal segment, though data in older humans is lacking. Second, we provide an exploratory analysis of hippocampal microstructure using indices from diffusion tensor MRI (DT-MRI).…”
Section: Introductionmentioning
confidence: 98%
“…Quantitative MR imaging confirmed the clinical interpretation that no gross brain atrophy was present, at least at 3.5 years following BB's steroid exposure. These radiological findings suggest that either: (1) the cognitive THE STEROID DEMENTIA SYNDROME 197 deficits were not related to structural injury, at least at the present macroscopic level of neuroimaging resolution; (2) neuronal damage and/or delayed development of neuronal function had occurred, and was present at the time of the quantitative MRI scan, but the volumetric analyses were unable to distinguish between viable neurons and proliferative glial cells; (3) hippocampal alterations had occurred, but these were reflected in regionally specific alterations in hippocampal morphology (e.g., anterior hippocampus: Wiedenmayer et al, 2006) rather than in whole hippocampal volume; (4) brain structural volume loss had occurred, and was present at the time of the quantitative MRI scan, but it would have been demonstrable only by comparison with BB's own premorbid MRI scan (which was not available); or (5) brain structural volume loss had occurred at the time of the steroid exposure but had recovered by the time of the quantitative MRI scan. In each of the adult cases of steroid dementia syndrome we previously described (Wolkowitz et al, 1997) and in certain cases described by others (Sacks & Shulman, 2005;Norra et al, 2006), standard brain MRI scans were also read as essentially normal, although in some cases, position emission tomography (PET) showed a mild decrease in bi-temporal and bi-parietal activity, SPECT showed non-specific diffuse patchy bitemporal and bitmporal hypoperfusion, and magneto-encephalography (MEG) showed mild slowing in the left posterior temporal area.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence is scant when looking at these associations in adolescents. A study of healthy pre-pubertal children found no relation between serum cortisol levels and hippocampal volumes, but did find a relationship between serum cortisol and regional variations in hippocampal surface morphology (inward or outward deformations of the hippocampus relative to a reference hippocampus), such that outward deformations of the anterior segment and inward deformations of lateral aspects of the medial segment were related to higher cortisol levels (Wiedenmayer et al, 2006). These associations have yet to be studied in an adolescent population.…”
Section: Introductionmentioning
confidence: 99%